Lessons on International Coordination from the Nepal Earthquake of 2015 (Unity Journal, 2025)
The International Community generally coordinate Humanitarian Assistance and Disaster Relief (HADR) operations relatively well between themselves, when working in failed state or intervention scenarios. However, the model for working through a functional, if temporarily degraded host nation, is less clear. The experience of the 2015 Nepal Earthquake, demonstrates the need for a more nuanced model for coordination in such scenarios. This paper highlights that related doctrine is currently suboptimal, and does not adequately consider that the host nation may well be in a stronger position to shoulder the burden of early operations. The analysis also indicates that assisting contingents may be unduly limited by their own governing policies. Importantly, most internationals tend to depart before alternate arrangements are fully in place, potentially leaving gaps for the host nation to fill. While the Nepal disaster is used to examine these issues, the lessons have implications for future HADR operations worldwide. Recommended measures include closer coordination to work with and through the host nation, a multinational military coordination center (MNMCC) framework, increased flexibility of deploying contingents, and the need for foreign contingents to help minimize any gaps when withdrawing, by working to enable the host nation from the outset.